Visionary leadership and digital competence on the effectiveness of Islamic boarding school education services - Zaenul Muttaqin; Widodo Widodo; Merry Lapasau; Hendro Prasetyono (Jurnal Konseling dan Pendidikan, 2026)
This meta-analysis synthesized empirical evidence on the association between visionary leadership, digital competence, and the effectiveness of educational services in Islamic boarding schools. Using the PRISMA 2020 guidelines, 30 peer-reviewed quantitative studies published between 2018 and 2026 were selected from eight electronic databases based on predefined inclusion criteria and extractable effect sizes. Effect sizes were converted to Pearson correlations and pooled using a random-effects model in Comprehensive Meta-Analysis Version 4. Subgroup analyses examined geographic region, institutional level, and research design, while publication bias was assessed using funnel plots and Egger's regression test. The pooled effect of visionary leadership was moderate and significant (r = 0.41, 95% CI [0.28, 0.52], p < .001), whereas digital competence showed a stronger significant association (r = 0.48, 95% CI [0.35, 0.59], p < .001). Both analyses exhibited substantial heterogeneity, with smaller effects observed in pesantren than in general Islamic school settings. These findings suggest that visionary leadership and digital competence are complementary factors associated with educational service effectiveness. Future longitudinal and quasi-experimental studies are needed to establish causal relationships.